Molecular Ultrathin Layers and Ordered Systems - Drahoslav Barancok; Julius Cirak; Pavol Tomcik; Marek Vanco (Communications - Scientific letters of the University of Zilina, 2003)
Monomolecular assemblies on substrates, now termed Langmuir-Blodgett (LB) films, exhibit many interesting properties and can perform functions which give them perspectives to impact advanced technologies and molecular electronics in an important way. In this article we briefly present our recent efforts aimed at the study of nanoelectric phenomena in the Langmuir monolayer formed on a water surface as well as electrochemical properties of Langmuir-Blodgett films deposited on the surface of an ultramicroelectrode involved in microsensors.